Company Performance Improvement Strategy Through Human Resource Management And Job Satisfaction And Its Impact On Employee Productivity - Bambang Suriadi; Maryam Batubara (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
One of the key issues in a company's success in achieving its vision and mission is the quality of Human Resources (HR). The Objektive of this study is to determine the importance of human resource management strategies and job satisfaction that has an impact the productivity of employees. 1. In this research, we observed the appliedship Human Resources on management of PT. Padasa Enam Utama Kebun Teluk Dalam), Based on target and its operation, 2. In this research, we prepare questionaire for our respondents which will be interviewed and the outcome will be used for the analysis on the achievement in company’s performance is probability the corporate productivity. 3. It can be identified what strategy does the company to achieve its vision and mission. 4. It can be concluded that the quality of human resources need to be improved the target on the company's performance from the point of the current performance